Efeito da adubação nitrogenada de diferentes espaçamentos entre plantas e da cobertura morta do solo sobre a produção do alho "amarante" - Alves de Menezes Sobrinho, João; Ferreira de Novais, Roberto; Lopes dos Santos, Hélio; Aguiar Sans, Luiz Marcelo (Revista Ceres, 2025)
The object of this study was to test the effect of mulch, three nitrogen levels (0,500 and 1000 kg ammonium sulfate/ha), and three in - row spacings (5.0,7.5 and 10.0 cm) on garlic yield, average bulb weight, number of bulbs per given area and on the straw/bulb ratio in different soils at different locations.